Comprehensive Analysis of Macroscopic and Microscopic Features ofSolanum Xanthocarpum Schrad. and J.C. Wendl. (Kantakari): Root,Leaf, Flower, Stem, and Fruit - Priya, Priya Gupta; Sonal, Dr Sonal Singh Kushwaha; Suman, Dr. Suman Panwar (International Research Journal of Ayurveda & Yoga, 2024)
This study provides a comprehensive analysis of the macroscopic and microscopic features of Solanum xanthocarpum Schrad. & J.C.Wendl., focusing on the root, leaf, petiole, seed, and fruit, while also incorporating an Ayurvedic perspective on its properties and actions. Solanum xanthocarpum Schrad. & J.C.Wendl., a vital plant in traditional medicine, exhibits distinct morphological and anatomical characteristics that contribute to its therapeutic properties. Macroscopic examination reveals the plant’s physical attributes, including size, shape, color, and texture of various parts. Microscopic analysis, utilizing advanced techniques, highlights the cellular structure and arrangement, elucidating key identifying features such as vascular bundles, trichomes, and stomatal patterns. From an Ayurvedic viewpoint, Solanum xanthocarpum Schrad. & J.C.Wendl. (commonly known as Kantakari) is renowned for its Vata and Kapha pacifying properties. It is traditionally used for its expectorant, anti-inflammatory, and diuretic actions. The plant is utilized in the management of respiratory conditions, such as asthma and bronchitis, and is also known for its beneficial effects on urinary and digestive systems. Understanding these characteristics is essential for accurate identification, quality control, and authentication of Solanum xanthocarpum Schrad. & J.C.Wendl. in pharmacognosy and herbal medicine. This detailed study enhances the knowledge base of medicinal plants and supports further research into the pharmacological potential of Solanum xanthocarpum Schrad. & J.C.Wendl., integrating both modern scientific insights and traditional Ayurvedic wisdom.